2020
DOI: 10.3390/polym12020252
|View full text |Cite
|
Sign up to set email alerts
|

Improved Nylon 6,6 Nanofiber Membrane in A Tilted Panel Filtration System for Fouling Control in Microalgae Harvesting

Abstract: The competitiveness of algae as biofuel feedstock leads to the growth of membrane filtration as one of promising technologies for algae harvesting. Nanofiber membrane (NFM) was found to be efficient for microalgae harvesting via membrane filtration, but it is highly limited by its weak mechanical strength. The main objective of this study is to enhance the applicability of nylon 6,6 NFM for microalgae filtration by optimizing the operational parameters and applying solvent vapor treatment to improve its mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 41 publications
(37 reference statements)
3
19
0
Order By: Relevance
“…The effect of the aeration rate was evaluated by comparing the steady state permeability at different air flow rates ( Figure 5). Overall, both PSF-1 and PSF-3 showed a steady increase in permeability with an increment in aeration rate, which is consistent with other findings [16,35,36]. An aeration rate of 1.8 L•min −1 improves water permeability by ±10% compared to the non-aerated system.…”
Section: Effect Of Aeration Ratesupporting
confidence: 90%
“…The effect of the aeration rate was evaluated by comparing the steady state permeability at different air flow rates ( Figure 5). Overall, both PSF-1 and PSF-3 showed a steady increase in permeability with an increment in aeration rate, which is consistent with other findings [16,35,36]. An aeration rate of 1.8 L•min −1 improves water permeability by ±10% compared to the non-aerated system.…”
Section: Effect Of Aeration Ratesupporting
confidence: 90%
“…On the other side, it is worth mentioning the eventual positive impact of the cake layer: A compact and more resistant cake layer acts as a secondary filtration layer, protecting the membrane surface from small organics molecules responsible for irreversible fouling (Low et al, 2016;Fortunato et al, 2020;Novoa et al, 2020). Javadi et al (2014) found out that an increase in the cake layer resistance, induced by a compact and nonporous structure, improved the permeate quality (Javadi et al, Fletcher et al, 2011a;Wang et al, 2014;Fortunato et al, 2017;Bagheri and Mirbagheri, 2018;Mat Nawi et al, 2020 Irreversible: removed by chemical cleaning…”
Section: (Table 1)mentioning
confidence: 99%
“…The membrane proprieties and configuration influence their surface properties and define the dominating fouling mechanism and overall fouling severity (Figure 3). The membrane materials directly impact properties, such as morphology (roughness, pore size, and distribution), hydrophilicity/hydrophobicity and electric charge (Liao et al, 2018;Zhang and Fu, 2018;Mat Nawi et al, 2020). On the other hand, membrane configuration also FIGURE 3 | Summary of fouling contributing factors in algal membrane separation processes.…”
Section: Impact Of Membranes On Algal Foulingmentioning
confidence: 99%
See 1 more Smart Citation
“…To deal with this problem, pursuit on the effective methods to reduce and control membrane fouling have been done through various endeavors [ 8 , 11 , 12 , 13 ]. Though the mechanism and behavior of fouling are complex, it has been widely reported that increasing the hydrophilicity of the membrane can be one of the viable solutions to limit the rate of foulant adsorption and thereby reducing the membrane fouling severity [ 14 , 15 , 16 , 17 , 18 , 19 ]. The enhancement of the hydrophilicity can be done by introducing a hydrophilic additive into the membrane materials through various techniques, such as blending [ 20 , 21 , 22 , 23 , 24 ], coating [ 25 , 26 ], grafting [ 27 ] and so forth.…”
Section: Introductionmentioning
confidence: 99%